PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KELAUTAN DAN PERIKANAN KABUPATEN DONGGALA - Ernawaty, Ernawaty; Natsir, Syahir; Miru, Sulaiman (Katalogis, 2018)
The study intends to determine and analyze simultaneous and partial influence of transformational leadership style, work culture, and discipline in marine and fishery Departmet in Donggala District. Sampel consists of 41 officials. Method of analysis is descriptive verificative with multiple linier regressions analysis. The result shows that transformational leadership style, work culture, and discipline simultaneously influence officials’ performance significantly with f value of 24.717 on sig 0.000; transformational leadership style influence performance significantly with t value of 2.337 on sig 0.025;, work culture influence performance significantly with t value of 2.753 on sig 0.009, discipline influence performance significantly with t value of 2.344 on sig 0.025.